Evaluation and modification of powertiller operated paddy reaper - Selvan P (Department of Farm Power Machinery and Energy, Kelappaji College of Agricultural Engineering and Technology, 1995)
The study on power tiller operated paddy reaper-windrower was taken up solve the problems of labour scarcity and uneconomic cost of cultivation of paddy. The 1.6 m vertical conveyer reaper-windrower was fabricated and was mounted with commercially available 8-10 hp air cooled Mistubishi power tiller. Improvements and modifications were carried out to make the unit suitable for harvesting of paddy in Kerala. The original engine chasis of the power tiller was replaced with a newly fabricated chasis on which both the engine and paddy harvester were mounted.